PELAYANAN SOSIAL SEKOLAH RAUDHATUL SA’ADAH DALAM PEMBERDAYAAN MASYARAKAT DI DESA CEMPLANG KECAMATAN JAWILAN KABUPATEN SERANG - Siti Nadiah (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2021)
The development of social welfare is a mandate for all countries in the world. Poverty is not only a lack of primary needs, health, and education. Poverty will give equality to various underdeveloped groups of people. Therefore, Raudhatul Sa’adah is a school that tries to ease the burden on the government to empower the community. This study aims to explain: 1) to find out the community in Cemplang Village, Jawilan District, Serang Regency, 2) to find out the social services provided by Raudhatul Sa’adah School in community empowerment. 3) to find out the economic condition of the community in Cemplang Village, Jawilan District, Serang Regency. This study used a qualitative method, because the author wanted to describe the objective of research based on the fact that occurred in the research place. As for the data collection techniques using observation, interviews and documentation. Based on the research that has been done, it can be concluded that Raudhatul Sa’adah School has a service program, namely an education program and an economic business service program. In the education service program, schools provide several services, namely reading glasses, early childhood, and children's scholarships, while in the economic business service program, nemely are benefits that are felt, namely the benefits of education and economic benefits. The supporting factors of the program are: involvement of good administrators and donor assistance. As for the inhibiting factors, nemely: lack of awareness in archiving data, people who have been empowered choose to live their respective lives, and lack of facilities and infrastructure.